Hexa-peri-hexabenzocoronene decorated with an allenylidene ruthenium complex – almost a flyswatter. Issue 37 (15th September 2020) - Lorenz, Rebecca; Reger, David; Weller, Ruth; Jux, Norbert; Burzlaff, Nicolai
Abstract : A ruthenium allenylidene complex bearing a hexa- peri -hexabenzocoronene (HBC) substituent was synthesised, resembling yet another strategy to decorate HBCs with transition metal fragments. Abstract : Carbon-rich ruthenium allenylidene complexes bearing either a hexaarylbenzene (HAB) or a hexa- peri -hexabenzocoronene (HBC) substituent were synthesised. This was achieved via the corresponding propargyl alcohols with HAB and HBC substituents, which were accessible via 3 or 4 step reaction cascades. Reaction of the propargyl alcohols HCC(OH)Ph(HAB) and HCC(OH)Ph(HBC) with [RuCl(η 5 -C5 H5 )(PPh3 )2 ] yielded the complexes [Ru(η 5 -C5 H5 )(CCC(HAB)(Ph))(PPh3 )2 ]PF6 and [Ru(η 5 -C5 H5 )(CCC(HBC)(Ph))(PPh3 )2 ]PF6 . The latter of which shows interesting π–π-stacking behaviour in the solid state as well as aggregation in solution.